Henipavirus pathogenesis and antiviral approaches. Issue 3 (March 2015) - Mathieu, Cyrille; Horvat, Branka
<x xml:space="preserve">Abstract</x> Hendra virus and Nipah virus are closely related, recently emerged zoonotic paramyxoviruses, belonging to the Henipavirus genus. Both viruses induce generalized vasculitis affecting particularly the respiratory tract and CNS. The exceptionally broad species tropism of Henipavirus, the high case fatality rate and person-to-person transmission associated with Nipah virus outbreaks emphasize the necessity of effective antiviral strategies for these intriguing threatening pathogens. Current therapeutic approaches, validated in animal models, target early steps in viral infection; they include the use of neutralizing virus-specific antibodies and blocking membrane fusion with peptides that bind the viral fusion protein. A better understanding of Henipavirus pathogenesis is critical for the further advancement of antiviral treatment, and we summarize here the recent progress in the field.